If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 12 + -1(3(x + -7)) = 0 Reorder the terms: 2x + 12 + -1(3(-7 + x)) = 0 2x + 12 + -1((-7 * 3 + x * 3)) = 0 2x + 12 + -1((-21 + 3x)) = 0 2x + 12 + (-21 * -1 + 3x * -1) = 0 2x + 12 + (21 + -3x) = 0 Reorder the terms: 12 + 21 + 2x + -3x = 0 Combine like terms: 12 + 21 = 33 33 + 2x + -3x = 0 Combine like terms: 2x + -3x = -1x 33 + -1x = 0 Solving 33 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33' to each side of the equation. 33 + -33 + -1x = 0 + -33 Combine like terms: 33 + -33 = 0 0 + -1x = 0 + -33 -1x = 0 + -33 Combine like terms: 0 + -33 = -33 -1x = -33 Divide each side by '-1'. x = 33 Simplifying x = 33
| 4a+19b= | | 3x^2+17x-8.1=0 | | 3(4x/5-1)=x | | 5c-10cd-15=0 | | 7x^2-x-4x=0 | | sin(pi/3x) | | 13d+8=8d+13 | | 8x^2-x-x^2=0 | | 71=8c-1 | | 8x^2-8-2x^2=0 | | -x-24x+x-15x= | | 8e-4=23.2 | | 3p=24.9 | | 23x+x-25x-6x= | | log(4x-1)+log(x+3)=1 | | 4b+4c+9a=100 | | 3(4+12x)-6(2x+3)=36+2(3x+2) | | 31=8c-9 | | -30x-4x-x+8x= | | 9e-4=68 | | f(x)=2x^2+16x+30 | | 2y+12=3(x-7) | | 2y+12=4(x-7) | | 0=-2u^2+6u^2 | | (7x-2)=(4x-3) | | x=10+-0.6666666667y | | x+1=-30 | | 0=-9a+9a-1 | | 0=2a-8a | | 2x+12=3(x-7) | | -8/11y=-24 | | x^2+2.76*x-0.33=0 |